Entre o consumidor e o produtor: Práticas, saberes e crenças de professores de língua portuguesa do ensino fundamental no trabalho com o letramento em marketing em sala de aula - Jônio Machado Bethônico (2014)
The centrality of consumption in our days and the omnipresence of discourses to stimulate buying takes us to questioning the role of the school in developing critical consciousness in children and teenagers, in face of marketing strategies and their own desires and consumption behavior. In order to verify if and how activities and discussions are proposed towards forming critical consumers during the years of Primary School, investigations were done since 2006 centered in Marketing Literacy. This concept was shaped to refer to the capacity to comprehend and position towards acts of communication of publicity character (in its various formats, contents, mediums) and towards raising awareness regarding social and personal issues involved in consumption (needs and desires, consumerism and waste etc.). The research here presented concentrated on the opinions of teachers from the Municipal Schools of Belo Horizonte about their practices, knowledge and beliefs in relation to this specific literacy. Data collecting was done in two stages: an exploratory study and another of qualitative character, through a survey with 336 teachers, has substantiated the conceiving of a framework for eight in-depth interviews. Also, it has been analyzed some acts related to consumption policies and education, especially the National Curricular Parameters to Primary Schools, recognizing the importance of the official curriculum for driving teaching practices. It has been referred as theoretical sources: (1) to deal with the present context, works from sociologists such as Zygmunt Bauman, Gilles Lipovetsky and Néstor Canclini, besides authors from the field of Cultural Studies (Henry Giroux and Douglas Kellner) and works on childhood marketing (by Marisa Vorraber Costa e Maria Luiza Belloni); (2) to approach literacy, Magda Soares, Roxane Rojo, Brian Street and scholars of Critical Literacy; (3) about teaching, Maurice Tardif, José Contreras, António Nóvoa, José Gimeno Sacristán and Phillipe Perrenoud. In raising the State-of-the-art in the Educational Field, articles presented at ANPEd and theses and dissertations available at CAPES were considered. The analyses centered in the interviews, revealed, for instance, that the texts of publicity character, even though they are common in the classroom, are usually printed and canonical (advertisement in newspaper and magazines, posters, packages) different from the present typical marketing strategies of the companies, which privileged the use of TV and internet, besides exploring other communication tools. Teachers allegations point to an unsystematic work, lined by pragmatism. The approach adopted by the teachers is usually superficial and restrict due to, for example, difficulty to deal with non-verbal language, to excessive content and infrastructural limitations. Although, it has also been reported practices ruled by long-term planning, of wide and interdisciplinary character. Finally, it has been identified direct relations between the teachers attitude as consumers and the way with which they deal with messages of advertisement and consumption in the class.